Centralized control with decoupling approach for large scale multivariable processes - Khandelwal, Shubham; Aldhandi, Suresh; Detroja, Ketan P. (TENCON ... IEEE Region Ten Conference, 2019)
A centralized PI control design methodology with easy applicability to small as well as large scale MIMO processes is proposed in this manuscript. The gain and phase margin tuning rule is deployed here to design the diagonal (D) PI controllers for the simple effective transfer function models (approximated for effective open-loop transfer functions). While accounting for the input-output coupling, the D controllers ensure robustness in the design along with good set-point tracking performance. The off-diagonal (OD) controllers in the centralized PI control framework are designed using the D PI controllers and the process steady-state gain. The OD controller design is carried out with an objective of minimizing the interaction effects. The performance of the proposed method is verified by simulation studies on various benchmark multivariable systems. Further, the robustness of the proposed method to uncertainties in the plant model is evaluated by performing closed-loop simulations subject to a plant-model mismatch of ±30%.